PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI: STUDI KUANTITATIF PADA PUSKESMAS BARANTI - Patmawati, Patmawati; Mustanir, Ahmad; Sinrang, Andi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study aims to analyze the influence of competence, motivation, work discipline, and work environment on the performance of employees at Baranti Community Health Center, Sidenreng Rappang Regency. A quantitative approach with a causal-associative design was employed. The population consisted of all health center employees, and a total sampling technique was used, allowing the entire population to serve as respondents. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression after passing validity, reliability, and classical assumption tests. The results show that competence, motivation, work discipline, and work environment each have a positive and significant effect on employee performance, both partially and simultaneously. Competence emerged as the most influential variable, followed by motivation, work discipline, and work environment. These findings highlight that improving employee performance in community health centers requires an integrated strategy focused on strengthening competence, enhancing motivation, enforcing discipline, and improving the work environment.